2013
DOI: 10.1371/journal.pone.0066138
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effect of a Functional Endothelium on the Development of In-Stent Restenosis

Abstract: Treatment of stenosed coronary arteries by balloon angioplasty and stenting results in arterial injury including severe damage to the endothelium at the site of treatment and initiates a complex cascade of inflammatory processes that may lead to the development of in-stent restenosis (ISR). Many clinical and biological factors involved in the progression of restenotic lesions have been studied in detail over the past few years but the mystery behind the pathophysiological mechanisms of this disease is still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 53 publications
2
91
0
Order By: Relevance
“…It is also crucial to comprehend that the newly regenerated endothelial layer is often dysfunctional [40]. This fact can play a key role in the restenotic process, when the uncontrolled neointimal formation is not stopped after the shear stress-induced "normal" re-endothelialization increased the flow velocity by decreasing the lumen diameter.…”
Section: Discussionmentioning
confidence: 99%
“…It is also crucial to comprehend that the newly regenerated endothelial layer is often dysfunctional [40]. This fact can play a key role in the restenotic process, when the uncontrolled neointimal formation is not stopped after the shear stress-induced "normal" re-endothelialization increased the flow velocity by decreasing the lumen diameter.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patient's age, general immune state, comorbidities, such as diabetes mellitus, and the different size of the plaque and injured area can strongly influence the speed of regeneration and degree of inflammation. 16,17 Thus, there seems to be a clear need for a reliable diagnostic assessment of endothelial regeneration, as well as for the individualization of postinterventional anticoagulant and anti-inflammatory therapy.…”
Section: Discussionmentioning
confidence: 99%
“…NO is produced by a functional endothelium in response to fluid shear stresses, higher concentrations of NO are assumed to arrest the cell cycle during the G1 phase and return the cell to a quiescent state. Further details related to the formulation of the cell cycle have been explained in our previous publication [12].…”
Section: Tissue Growth Modelmentioning
confidence: 99%
“…Therefore, we assume that any endothelium which is not yet mature/functional does not play a significant role. The generation of NO from shear stress has been estimated by extrapolating the data provided by Guo et al [30], these details are reported in our previous paper [12]. Nakazawa et al [31] observed the time course of endothelial regeneration in stented porcine coronary arteries and assessed its functionality by means of platelet endothelial cell adhesion molecule (PECAM-1).…”
Section: Endothelium Regeneration and Smooth Muscle Cell Regulationmentioning
confidence: 99%